Pengembangan Media SBDP KIT Seni Rupa Materi Kerajinan Daur Ulang Kurikulum Merdeka Kelas IV - Ratih Fadhlika; Rofian; Kiswoyo (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This research describes the problems of (1) development of SBdP KIT media, (2) feasibility of SBdP KIT media. The aim of this research is to determine the process of developing SBdP KIT media and to determine the feasibility of media. The method used in this research is R&D carried out in five from the Borg & Gall model. Data collection techniques used interviews, observation and questionnaires, were analyzed using qualitative and quantitative descriptive data analysis techniques. Data validity uses validation and response techniques. The research was carried out at SD Dumpil and SD Alasdowo 01 in class IV. The results of the research explain the development and results of the SBdP KIT media field trials based on the results of teacher and student response questionnaires at SD Dumpil and SD Alasdowo 01 with percentages of 95% and 97% with the criteria "very feasible" for teacher responses. Student responses were 93% and 89% with the criteria "very feasible" involving 12 students from SD Dumpil and 14 students from SD Alasdowo 01. It is hoped that the media will be useful and can become a medium for students to be more creative in making handicrafts, especially in Fine Arts subjects with recycled craft materials.